Determinação do modelo de velocidades de migração por focalização de difrações geradas usando os atributos do operador CRS - Silva, José Silas dos Santos (2023)
The pre-stack migrated image in the time domain is still the main output in the processing of onshore seismic data, and a reliable migrated image of the subsurface depends on the accuracy of the migration velocity model. This model is difficult to determine, especially when it has to deal with low quality data, so we propose and evaluate two methods for determination of migration velocity model based on kinematic wavefield attributes used by the Common Reflection Surface (CRS) stacking method. These attributes, which are extracted from multicoverage data through global optimization, provide information about the local properties of the reflectors. However, there is no appropriate method that uses these attributes to determine the time domain migration velocity model. We present two practical methods to determine the time domain migration velocity model based on the application of wavefront attributes and the CRS stacking operator, the first by means of an automatic calculation and the second by means of generation of synthetic diffractions in the CRS stacked section reflection events with zero source-receiver offset. In zero-offset staked data with synthetic diffractions, the post-stack migration is applied at a set of constant velocities, and the migration velocities are selected through a simulated diffraction focusing analysis. We demonstrate the accuracy of the proposed algorithms using two synthetic models that represent geological structures with faults and folds. We also apply the method to low quality real 2D land seismic data to estimate the time domain migration velocity model. The velocity models obtained through the proposed methods were validated by applying them to the Kirchhoff pre-stack migration in the time domain, which provided significant improvements in the migrated image using the velocity model obtained by diffraction focusing.